Efeito in vitro da terapia fotodinâmica sobre bactérias orais em suspensão e na formação de biofilme : ensaio com azul de metileno e toluidina ativados por luz halógena - Dantas, Emanuelle Dayana Vieira (2011)
Photodynamic therapy (PDT) has been proposed as an alternative method for the treatment of biofilm-dependent oral diseases like dental caries. This therapy consists of simultaneous action of a visible light (L) and a photosensitizer (FS) in the presence of oxygen, which leads to production of different reactive oxygen species that can interact with the bacterial cell components, and promote cell death. This study aims to evaluate the antimicrobial action of PDT on oral bacteria in suspension, as well as the formation of mono and multi-species biofilms, in vitro, from a standard strain of Streptococcus mutans (ATCC 25175) and saliva samples, respectively. The dye methylene blue (MB) and toluidine blue (TB) were used at a concentration of 100 mg/ L and activated by halogen light (600 to 750 nm) from a modified hand held photopolymerizer (Ultralux ®, Dabi Atlante, Ribeirão Preto , São Paulo, Brazil.). Planktonic cultures were prepared and submitted to different experimental conditions: 1. PDT using TB 2. PDT using MB, 3. L+ FS- , 4. TB + L - ; 5. MB+ L-; 6. L- FS- (negative control) and 7. administration of 0.12% chlorhexidine digluconate (positive control) (Periogard ®, Colgate-Palmolive Company, New York, USA). The immediate and mediated action of PDT on bacterial suspensions, as well as its effect on biofilm formation were observed from the number of colony-forming units per milliliter (CFU/mL) and measures optical density (OD). The data were statistically analyzed using the Kruskal-Wallis and Mann-Whitney test for the significance level of 5%. According to the results, the PDT showed no antibacterial action on suspensions of S. mutans, regardless of the dye used. PDT with MB activated by halogen light was able to reduce 86.6% CFU/mL multi-species planktonic cultures, however, this reduction was not significant (p > 0.05). PDT showed antibacterial effect, mediate on multi-species planktonic cultures with TB (p < 0.001) and MB (p < 0.001), activated by halogen light. PDT was able to prevent the formation of multispecies biofilm, through the activation of TB by halogen light (p = 0.01). We conclude that activation of the dye toluidine blue and methylene blue, by halogen light (PDT) showed antimicrobial activity, compared to multi-species planktonic cultures prepared from saliva samples